Photoelastic Analysis of the Influence of Platform Switching on Stress Distribution in Implants - Pellizzer, Eduardo Piza [UNESP]; Falcon-Antenucci, Rosse Mary; Perri de Carvalho, Paulo Sergio [UNESP]; Santiago, Joel Ferreira; Dantas de Moraes, Sandra Lucia; de Carvalho, Bruno Machado (Allen Press Inc, 2010)
The aim of this study was to evaluate the stress distribution of platform switching implants using a photoelastic method. Three models were constructed of the photoelastic resin PL-2, with a single implant and a screw-retained implant-supported prosthesis. These models were Model A, platform 5.0 mm/abutment 4.1 mm; Model B, platform 4.1 mm/abutment 4.1 mm; and Model C, platform 5.00 mm/abutment 5.00 mm. Axial and oblique (45 degrees) loads of 100 N were applied using a Universal Testing Machine (EMIC DL 3000). Images were photographed with a digital camera and visualized with software (AdobePhotoshop) to facilitate the qualitative analysis. The highest stress concentrations were observed at the apical third of the 3 models. With the oblique load, the highest stress concentrations were located at the implant apex, opposite the load application. Stress concentrations decreased in the cervical region of Model A (platform switching), and Models A (platform switching) and C (conventional/wide-diameter) displayed similar stress magnitudes. Finally, Model B (conventional/regular diameter) displayed the highest stress concentrations of the models tested.
Keywords: dental implants; biomechanics; platform switching; photoelastic stress analysis